2017
DOI: 10.1242/bio.025833
|View full text |Cite
|
Sign up to set email alerts
|

A reporter mouse model forin vivotracing andin vitromolecular studies of melanocytic lineage cells and their diseases

Abstract: Alterations in melanocytic lineage cells give rise to a plethora of distinct human diseases, including neurocristopathies, cutaneous pigmentation disorders, loss of vision and hearing, and melanoma. Understanding the ontogeny and biology of melanocytic cells, as well as how they interact with their surrounding environment, are key steps in the development of therapies for diseases that involve this cell lineage. Efforts to culture and characterize primary melanocytes from normal or genetically engineered mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The propensity of melanoma cells to metastasize has been attributed, in part, to their ability to interact with and modify their surrounding extracellular matrix, and to their imprinted high migratory capacity, arising from the embryonic neural crest cells that give rise to melanocytic cells [25]. Cultured melanocytes exhibit marked differences in migratory capacity, depending on the substrate on which they are seeded [26]. Consequently, we first determined the effect of various extracellular substrates on motility of parental 131/4-5B1 cells using time-lapse videomicroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The propensity of melanoma cells to metastasize has been attributed, in part, to their ability to interact with and modify their surrounding extracellular matrix, and to their imprinted high migratory capacity, arising from the embryonic neural crest cells that give rise to melanocytic cells [25]. Cultured melanocytes exhibit marked differences in migratory capacity, depending on the substrate on which they are seeded [26]. Consequently, we first determined the effect of various extracellular substrates on motility of parental 131/4-5B1 cells using time-lapse videomicroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma cell interactions with ECM proteins present in the skin, such as collagen IV and laminin 332, are important for cell migration and invasion. We have observed that both normal primary cultured melanocytes and parental 131/4-5B1 melanoma cells exhibit greater motility on laminin 332 compared to collagen I ([26] and Figure S2). Similarly, A375 and other melanoma lines show enhanced haptotactic migration in response to laminin 332, relative to collagen and other ECM substrates, a response likely mediated through α3β1 integrins [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of ILK in melanosome trafficking, we isolated primary Tyr::CreER T2 ;ROSA mT/mG ;Ilk f/f melanocytes and cultured them to >95% purity, as we previously described (Crawford et al, 2017). In the absence of CreER T2 activation, these cells express a membrane-bound form of Tomato fluorescent protein (mTomato) (Crawford et al, 2017).…”
Section: Altered Melanosome Dynamics In Ilk Ko Melanocytesmentioning
confidence: 99%
“…Experimental animal models also proved to be reliable sources of data concerning (i) the screening for novel antimelanoma agents: temozolomide (B16F10 metastatic melanoma model) [ 66 , 67 ], thymoquinone (B16F10 intracerebral melanoma model using C57BL/6J mice as host) [ 68 ], oncolytic herpes simplex virus HF10, and dacarbazine combined therapy (DBA/2 mice subcutaneously inoculated with clone M3 mouse melanoma cells) [ 69 ], gliotoxin (a xenograft mouse model using athymic mice) [ 70 ], recombinant methioninase [ 71 ], cancer vaccines [ 72 ], natural compounds [ 73 , 74 ]; (ii) molecular discovery—the comprehension of melanoma metastatic pathway involving microvascular environment [ 75 ]; and (iii) in vivo tracing of melanocytic lineage cells [ 76 ].…”
Section: Murine Models Of Melanomamentioning
confidence: 99%